Relationship Between Locomotor Functional Capacity and Obesity Degrees in Adult Argentine Women - Sacerdoti, Alina; Frechtel, Gustavo; español (Revista de Salud Pública, 2023)
Introduction: Individuals with obesity experience a decrease in their locomotor functional capacity compared to those without overweight. It is not clear whether, in people with obesity, this capacity is related to the degree of obesity. Objective: To analyze the relationship between obesity degrees according to different anthropometric indicators and locomotor functional capacity. Methodology: Fifty-three voluntary adult women (46.3±8.0 years old) with a body mass index (BMI) equal to or greater than 30 participated in the study (n=20 with obesity grade I; n=17 with obesity grade II; n=16 with obesity grade III). Weight, height and waist circumference were measured and the 6-minute walk test, and timed up-and-go test were taken. Results: Statistically significant associations were found between different obesity indicators and locomotor functional capacity, especially in the 6-minute walk test and BMI. These correlations remained significant even in individuals without diabetes, without metabolic syndrome, and who had not reached menopause. Conclusions: In adult women with obesity, locomotor functional capacity decreases as the degree of obesity increases, even in individuals without metabolic disorders or advanced age. Therefore, any reduction in the degree of obesity is advisable, even in individuals who may not achieve a non-obese situation.